2009
DOI: 10.1021/la802870z
|View full text |Cite
|
Sign up to set email alerts
|

Confined Self-Assembly of Toric Focal Conic Domains (The Effects of Confined Geometry on the Feature Size of Toric Focal Conic Domains)

Abstract: A smectic liquid crystal (LC) containing a rigid biphenyl group and semifluorinated chains exhibits a high density of toric focal conic domains (TFCDs) arranged in an ordered array when confined within a microchannel. The formation of the TFCDs is strongly influenced by the width (W) and depth (h) of the confined microchannels, most importantly, by the channel depth. We studied a broad variety of microchannels, with varying width in the range of 3-200 mum and depth in the range of 2-10 mum. The radius of the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
83
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 41 publications
3
83
0
Order By: Relevance
“…Highly ordered hexagonal arrays of TFCDs were observed on bare Si wafers and SU-8 coated Si wafers via scanning electron microscopy (SEM) with corresponding Maltese cross patterns in polarized optical microscopy (POM) (see Figure S3a-c, Supporting Information). The same morphology has been reported by Kim et al [ 23 ] on Tefl on amorphous fl uoropolymer coated Si and glass substrates, suggesting high planar anchoring strength of the LCs on these substrates. It has been suggested that the TFCD radius a , measured as half of the center-tocenter distance between neighboring TFCDs, is roughly equal to half of the LC fi lm thickness ( h ) in these regions.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…Highly ordered hexagonal arrays of TFCDs were observed on bare Si wafers and SU-8 coated Si wafers via scanning electron microscopy (SEM) with corresponding Maltese cross patterns in polarized optical microscopy (POM) (see Figure S3a-c, Supporting Information). The same morphology has been reported by Kim et al [ 23 ] on Tefl on amorphous fl uoropolymer coated Si and glass substrates, suggesting high planar anchoring strength of the LCs on these substrates. It has been suggested that the TFCD radius a , measured as half of the center-tocenter distance between neighboring TFCDs, is roughly equal to half of the LC fi lm thickness ( h ) in these regions.…”
supporting
confidence: 86%
“…[ 23 ] They found that an energetically stable, hexagonal array of TFCDs is formed when W and H are above the critical values, W c ≈ 4 μ m and H c ≈ 2 μ m. [ 23 ] Here, we use SU-8 pillar arrays with varying pillar diameter, height, spacing, and symmetry as a 3D confi nement system for SmA LCs. Figure 1 , 2 demonstrate different TFCD morphologies from the assembly of SmA LCs directed by confi nement and interaction with the underlying square pillar arrays at variable length scales.…”
mentioning
confidence: 99%
“…The remnant structure was observed under polarized light microscopy (PLM) as an evolution of the optical texture, and with suboptical resolution using EM and AFM techniques to probe the remnant interface topographic structure. Experiments reported here show that sublimation is useful for visualizing 3D layering and should be broadly applicable to the study of soft matter structure when combined with available fixing and visualization methods (11)(12)(13)(14)(15).…”
mentioning
confidence: 91%
“…These TFCD arrays have been used to fabricate functional surfaces (19,20), to direct the self-assembly of soft microsystems (17,21,22), to template lithographic patterns (23), and to enhance charge transport in photovoltaics and transistors (24). So far, most attention has been devoted to the precise manipulation of the locations of FCDs in 2D lattices by confining individual domains within small regions through both chemical and topographical patterning of the substrate (14,15,25). For device applications, it is desirable to produce FCDs with prescribed arrangements in 2D and 3D over large regions and to scale down the LC patterning.…”
mentioning
confidence: 99%